The Influence of Sales Promotion and Quality of Tile Products on Consumers' Interest To Buy at CV Maestro Atop Bekasi - Isna Hanifah, Isna Hanifah; Asim; Nurminingsih; Kwaranto Rohmawan (Journal of Entrepreneur and Business, 2023)
Roofing businesses or businesses in Indonesia have developed quite rapidly in recent years, with various formats and types. In the midst of Indonesia's economic conditions which are experiencing difficult times, the roofing business can still survive because everyone definitely needs housing, for example. The Rooftop retail business has even more potential to develop, as evidenced by the proliferation of this business from big cities to small towns. CV. Maestro Atap Bekasi is a company that sells roof tiles, pvc, tile accessories. The purpose of this study was to determine and analyze the influence of sales promotion and product quality on consumer buying interest in CV. Maestro Roof Bekasi. There are several variables that are connected, namely Sales Promotion (X1), Product Quality (X2), and Purchase Interest (Y). This method uses quantitative methods. The population in this study is Consumer CV. Maestro Roof Bekasi with a total sample of 79 respondents. Data collection techniques by distributing questionnaires. The results of data analysis show that Sales Promotion has a positive and significant direct effect on Buying Interest. Product quality has a positive and significant direct effect on Purchase Intention. And UK Sales Promotion has a positive and significant direct effect on product quality. Keywords: Effect of Sales Promotion and Product Quality on Purchase Intention